Strengthening Organizational Commitment Among Vocational School Teachers: The Roles of Personality, Leadership, Culture, and Job Satisfaction - Griet Helena Laihad; Soewarto Hardhienata; Tiarma Ika Yuliana (STAI Hubbulwathan Duri, 2025)
This study aims to identify strategies for increasing organizational commitment among permanent foundation teachers at Private Vocational Schools of Computer Engineering and Networking (TKJ) in East Jakarta. A quantitative approach was utilized, employing path analysis on a sample of 195 teachers selected from a population of 381. The findings revealed several significant relationships. Personality had a strong and positive direct effect on organizational commitment (β = 0.737, p 0.05), while transformational leadership also had a positive, albeit smaller, impact (β = 0.089). Organizational culture contributed meaningfully (β = 0.263), and job satisfaction showed a moderate influence on commitment (β = 0.193). Furthermore, personality was positively related to job satisfaction (β = 0.287), as were transformational leadership (β = 0.142) and organizational culture (β = 0.508). Mediation analysis indicated that job satisfaction effectively mediated the relationship between personality and organizational commitment (Z = 3.44 1.96; β = 0.144). However, it did not mediate the relationship between transformational leadership and commitment (Z = 0.991 1.96; β = 0.017). For organizational culture, the mediation effect of job satisfaction was marginal (Z = 1.957 1.96; β = 0.039). These results suggest that enhancing teacher personality traits, fostering a supportive organizational culture, and improving job satisfaction are key strategies to strengthen organizational commitment in TKJ vocational schools.